Effect of sodium-glucose cotransporter type 2 inhibitors on renal outcome: An integrative review (Research, Society and Development, 2023)
Chronic kidney disease (CKD) is characterized by progressive kidney damage with a drop in glomerular filtration rate for a period longer than three months. Among the main causes of CKD in the Brazilian population are type 2 diabetes mellitus (DM2) and systemic arterial hypertension (SAH). Drug therapy with Sodium-glucose cotransporter type 2 inhibitors (iSGLT-2) allows control of the loss of renal function and decreases the need for patients to need renal replacement therapy such as hem dialysis. Objective: To understand the effects of iSGLT-2 in reducing renal outcome, in order to know its benefits and adverse events. Methodology: This is an integrative literature review from the january 2017 to january the 2022, in the electronic databases SCIELO, PUBMED and LILACS, including work in Portuguese and English. The flow diagram was used as a tool for organizing and analyzing the articles. The works of interest were analyzed and then the results with their respective bibliographic data were organized in a frame. Results: Twelve randomized clinical trials were analyzed, of which 5 (42%) studies on canagliflozin, 4 (33%) studies on dapagliflozin, 2 (17%) on empagliflozin and only 1 (8%) study on ertugliflozin. Conclusion: SGLT-2 inhibitors are a new class of drugs that have been shown in several studies to reduce unfavorable renal outcomes, with few side effects, proving to be an important therapeutic tool in the treatment of the population of patients with renal disease.